2012
DOI: 10.1155/2012/903645
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Experience with a Family Member with Alzheimer’s Disease on Views about the Disease across Five Countries

Abstract: The objective of this paper is to understand how the public's beliefs in five countries may change as more families have direct experience with Alzheimer's disease. The data are derived from a questionnaire survey conducted by telephone (landline and cell) with 2678 randomly selected adults in France, Germany, Poland, Spain, and the United States. The paper analyzes the beliefs and anticipated behavior of those in each country who report having had a family member with Alzheimer's disease versus those who do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…The following data are from a survey conducted by the Harvard School of Public Health on the public perceptions and awareness of AD [70]. The poll was commissioned by Alzheimer Europe through a grant provided by Bayer.…”
Section: Value Of Knowingmentioning
confidence: 99%
“…The following data are from a survey conducted by the Harvard School of Public Health on the public perceptions and awareness of AD [70]. The poll was commissioned by Alzheimer Europe through a grant provided by Bayer.…”
Section: Value Of Knowingmentioning
confidence: 99%
“…The following data is from a survey conducted by the Harvard School of Public Health on the public perceptions and awareness of Alzheimer’s disease [70]. The poll was commissioned by Alzheimer Europe through a grant provided by Bayer.…”
Section: Amyloid Pet and Anticipated Impact On Patient Carementioning
confidence: 99%
“…By unifying the message from clinical research we can increase the awareness of AD clinical trials taking place. Increasing awareness will improve public understanding towards the severity of the disease as it has been shown that individuals with close personal ties to patients with AD are more likely (than those without) to view AD as a major concern [63]. Consequently, this will not only reduce the number of undiagnosed individuals but will also serve to improve willingness to pursue predictive genetic and biomarker testing that may facilitate future asymptomatic enrollment.…”
Section: Social Legal and Policy Challengesmentioning
confidence: 99%